2000
DOI: 10.1002/1097-4636(20000915)51:4<650::aid-jbm13>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the nature of property gradients in the human dentine

Abstract: We conducted an investigation into the nature of dentine mineralization and mechanical property gradients with the aid of experimental techniques such as the fluoroscopic X-ray microanalysis and instrumented microindentation, respectively. It was found that the tooth adapts to a complex structure with significant gradients in properties. We observed a significant correlation between the degree of mineralization within the dentine and the mechanical properties. The natural gradation in mechanical properties is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 20 publications
1
54
0
1
Order By: Relevance
“…(3), which was derived from pure HA tablets, can still be applied without corrections for the organic matrix and water content for converting the attenuation coefficient of dentin into the corresponding elastic modulus. The results showed that the distribution of elastic modulus in the dentin followed a similar trend to that in enamel, where the outer dentin was harder than the inner dentin, as found in previous studies [6,23,26].…”
Section: Xxxe8mentioning
confidence: 99%
See 3 more Smart Citations
“…(3), which was derived from pure HA tablets, can still be applied without corrections for the organic matrix and water content for converting the attenuation coefficient of dentin into the corresponding elastic modulus. The results showed that the distribution of elastic modulus in the dentin followed a similar trend to that in enamel, where the outer dentin was harder than the inner dentin, as found in previous studies [6,23,26].…”
Section: Xxxe8mentioning
confidence: 99%
“…Fong et al [5] also reported that the nanohardness across the DEJ gradually decreased from 4.8 GPa to 0.8 GPa, with the elastic modulus following a similar profile. Kishen et al [6] found a significant correlation among the mineral density, hardness and elastic modulus in human dentin using fluoroscopic X-ray imaging and microindentation. Their results showed that the hardness and elastic modulus of root dentin increased gradually from the central region to the outer surface of the root.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The unique tubular structure of dentine is mainly related to evolutionar functional adaptation to enable mastication by transducing bite pressures into tensile forces in the collagen matrix [1]. In addition, fluid-filled dentinal tubules allow for transducing stimuli to the underlying pulp [2].…”
Section: Introductionmentioning
confidence: 99%